Opening GIScience: A process-based approach. Issue 10 (3rd October 2018) - Shannon, Jerry; Walker, Kyle
ABSTRACT: Many scholars have demonstrated growing interest in GIScience in recent years, including use of open data portals, shared code and options for open access publication. These practices have made both research and data more transparent and accessible for a broad audience. This research may be open only in a limited sense for populations without expertise in the technology and methods undergirding these data. Based on two case studies using RStudio's Shiny web platform, we argue that a process-based approach focusing on how analysis is opened throughout the research process provides a supplementary way to define and reflect upon public facing geographic research. Reflecting upon decisions we made at key points in each case study project, we identify four key tensions inherent to work in open GIScience: standardized vs. flexible tools, expert vs. community-led design, single vs. multiple audiences and established vs. emerging metrics.